Endothelial Dysfunction Induced by Cadmium and Mercury and its Relationship to Hypertension - Martins, Airton C.; Santos, Alessanda A.D.; Lopes, Ana C.B.A.; Skalny, Anatoly V.; Aschner, Michael; Tinkov, Alexey A.; Paoliello, Monica M.B. (Current Hypertension Reviews, 2021)
Hypertension is an important public health concern that affects millions globally, leading to a large number of morbidities and fatalities. The etiology of hypertension is complex and multifactorial, and it involves environmental factors, including heavy metals. Cadmium and mercury are toxic elements commonly found in the environment, contributing to hypertension. We aimed to assess the role of cadmium and mercury-induced endothelial dysfunction in the development of hypertension. A narrative review was carried out through database searches. In this review, we discussed the critical roles of cadmium and mercury in the etiology of hypertension and provided new insights into potential mechanisms of their effect, focusing primarily on endothelial dysfunction. Although the mechanisms by which cadmium and mercury induce hypertension have yet to be completely elucidated, evidence for both implicates impaired nitric oxide signaling in their hypertensive etiology.
Keywords: nitric oxide